Creación de prototipos virtuales multinivel del sistema de actuación electromecánica para aviones eléctricos (2021)
Electromechanical actuators (EMA) are becoming increasingly attractive in the field of more electric aircraft due to their exceptional benefits, which include lower fuel consumption and maintenance costs, increased system flexibility, and improved fault detection and isolation management. However, electromechanical actuation poses specific problems when used for safety-critical aerospace applications such as flight controls: large load-reflected inertia, interference-type failure, and increased backlash with service due to wear and local heat loss dissipation for thermal equilibrium. This study proposes an incremental approach to AEM virtual prototyping. It is driven by a modelbased systems engineering process to enable simulation-aided design.